PENEGAKAN HUKUM TERHADAP NOTARIS YANG MEMPROMOSIKAN DIRI MELALUI MEDIA SOSIAL - Riyan Saputra; Gunawan Djajaputra (Fakultas Hukum Universitas Tarumanagara, 2018)
Notary is a carrier of office or ordinary we call the general officer appointed by the state and also work for the service of the public interest, in carrying out its duties a Notary must adhere to the rules of legislation that prevail in Indonesia as he served. In the Notary Code of Ethics and the Decree of the Minister of Justice and Human Rights of the Republic of Indonesia there is a provision that prohibits a Notary from conducting a form of promotion in social and electronic media, what are the constraints faced by the Notary Supervisory Board in Indonesia? The author examines the problem using normative legal research methods supported by some interviews that are expected to help answer the research and sources interviewed are the parties concerned such as Kaskus, Supervisory Board and also one of Notary in Jakarta. Subsequently, the acts committed by the Notary are clearly violated and appropriate to the sanction imposed on such notary as regulated in Article 6 paragraph (1) of Notary Code and Article 18 Paragraph (4). In this case it is clear that the Notary was found guilty of a form of self-promotion in Social Media, but the Supervisory Board itself essentially oversees the Notary but due to the many obstacles faced by the Supervisory Board, the duties of the Supervisory Board itself do not alter Board regulations Notary Supervisors become more assertive and expected to apply optimally.